NON-STANDARD FORMS OF EMPLOYMENT IN THE POST-CRISIS ECONOMY - Гайдар, А. Е. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2014)
Influenced by post-crisis state and the growing pace of globalization, employment system under goes drastic changes in its content and structure. The main feature of today’s labour market is the development of non-standard forms of employment, hence the need to study the essence of the se tumors.